Benzotriazole (BTA) as corrosion inhibitors encapsulated in the micro/nanocontainer for smart coating: A review - Nurul Shuhada, Mohamed; Juliawati, Alias (2022)
The development of functional smart coating with the ability for active anti-corrosion and selfhealing are significant for long term performance of numerous engineering application. Smart coating is a multifunctional coating containing self-healing chemical and corrosion inhibitor incorporated into the coating, allowing the metallic structure to recover from any damages. The most important aspect in developing smart coating is creating micro/nano-container that are compactible to encapsulate and sustain the active substance by having permeability shell that can respond to the external stimuli. Benzotriazole (BTA) has been extensively studied as corrosion inhibitor to regulate of iron, steel, copper, nickel, aluminum, and zinc by the formation of a protective surface film. This review presents the fabrication technique of the BTA loaded micro/nano-container, characterization of the chemical structure and evaluation of the corrosion performance.